Village Resource Profile for Speed-up Information Delivery - Noviansyah, Deri (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2025)
In many rural areas of Indonesia, accessing accurate and timely information about village resources remains a significant challenge due to scattered data records, limited digital infrastructure, and slow manual processes. To address these issues, this study proposes a Village Resource Profile for Speeding Up Information Delivery, a system designed to centralize and streamline village data management. By integrating digital tools, this system facilitates efficient resource allocation, enhances development planning, and supports better decision-making for local governments, businesses, and residents.The study builds upon previous research in smart villages, rural governance, and geotourism management, emphasizing the role of ICT and data-driven strategies in rural development. The proposed system consists of multiple modules, including data collection, information processing, and service distribution, ensuring that essential information—such as population demographics, economic activities, and public services—is readily available.By leveraging real-time updates and AI-driven insights, the system improves access to critical information, enhances disaster preparedness, and promotes equitable public service distribution. This initiative aligns with Indonesia’s Smart Village program, fostering digital transformation at the grassroots level.